From house to school: the process of training and professionalization of teachers in Riachuelo/RN (1960-1980) (Research, Society and Development, 2018)
This paper aim to understand the process of pedagogical training and professional of some teachers in the city of Riachuelo-RN between 1960s to 1980s decades. In this sense it approaches the history of education in the context of RN's countryside, discussing the elements of education itself, local aspects and the training of the first classrooms in this municipality, therefore forming the school culture training process. The used methodology was oral history as a method of interviews, the technique of discourse analysis and teacher's memory analysis, research and bibliographical reading regarding to history of education. As theoretical basis we worked with the conception of History and Memory of Jacques Le Goff, the concept of School Culture of Dominique Julia, for covering a bigger space in the school culture, the context and the school environment and oral history of José Carlos Meihy, indispensable for the procedures of interview as transcriptions, assignment letter, among others. As an initial result of this research, it was identified two important educational projects for lay teachers, the SACI project and the Logos II project, which fulfill a big demand in this teacher training and was were fundamental for this process. With regard to the process of teachers training we will also discuss partly the professionalization process.